PERAN PEREMPUAN DALAM MENGEMBANGKAN PROGRAM PEMBERDAYAAN PEREMPUAN MELALUI MULTIMEDIA - Emilia Ramadhani (PERSPEKTIF, 2016)
This study aims to unify ideas or thoughts that will be developed in the movement of Indonesian women academics to women's empowerment program, particularly through the media.The approach will be used in this study is to model the quantitative and qualitative approach in social policy research. The population in this study were all female academics in the city of Medan with the characteristics of women who are actively teaching professor at the PTN and PTS in the shade Kopertis region I. The results showed that women academics agreed to unify their thoughts or ideas through the movement of women academics in an effort to empower women. Also it is known that during this activity was limited to female academics in the field activities with NGOs and for the contribution of ideas or thoughts are said to be less or very low. Then the media deemed appropriate to be used as a vessel to channel the ideas and thoughts about women are in the form of a multimedia website, in this case made gap-indonesia.org domain.